1994
DOI: 10.1128/mcb.14.4.2447
|View full text |Cite
|
Sign up to set email alerts
|

rac p21 is involved in insulin-induced membrane ruffling and rho p21 is involved in hepatocyte growth factor- and 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced membrane ruffling in KB cells.

Abstract: Insulin and hepatocyte growth factor (HGF) induced morphologically different membrane ruiflings in KB cells. Insulin-induced membrane ruffling was inhibited by microinjection of rho GDI, an inhibitory GDP/GTP exchange regulator for both rho p21 and rac p21 small GTP-binding proteins, but not inhibited by microinjection of botulinum exoenzyme C3, known to selectively ADP-ribosylate rho p21 and to impair its function. This rho GDI action was prevented by comicroinjection with guanosine 5'-(3-O-thio)triphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 56 publications
7
108
1
Order By: Relevance
“…Thus, RhoA activation is coincident with barbed end formation in MTLn3 cells in response to EGF stimulation [2]. The finding of activated RhoA in EGF-stimulated protrusions is consistent with recent reports implicating RhoA activity at the leading edge of moving cells [17,19,47,48].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, RhoA activation is coincident with barbed end formation in MTLn3 cells in response to EGF stimulation [2]. The finding of activated RhoA in EGF-stimulated protrusions is consistent with recent reports implicating RhoA activity at the leading edge of moving cells [17,19,47,48].…”
Section: Discussionsupporting
confidence: 90%
“…39 Rho activation is also involved in hepatocyte growth factor-and phorbol ester-induced membrane ruffling in epidermoid carcinoma cells. 40 Moreover, several reports have indicated that Rho is involved in the motility of several types of cells including neutrophils, 41 endothelial cells, 42 fibroblasts, 43 keratinocytes, 44 and some colon cancer cells (Sakamoto M, Hirohashi S, unpublished observation, 1996). However, it is still unclear how each member of the small GTPases is involved in the motility of different kinds of cells, or how cell adhesion and cytoskeletal systems are coordinated, especially in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts, membrane ruffling is stimulated by several growth factors, including IGF-I (Kotani et al, 1994;Wennström et al, 1994). In nonneuronal cells, activation of P1 3-K is necessary for membrane ruffling by acting as an upstream regulator of the small GTPase protein, Rac (Kotani et al, 1994;Nishiyama et al, 1994;Wennstrdm et al, 1994;Hawkins et al, 1995;Parker, 1995). We are currently investigating the role of P1 3-K activation of Rac in IGF-I-mediated changes in neuronal architecture (Kim et al, 1996).…”
Section: Discussionmentioning
confidence: 99%